New user? Sign up

Existing user? Sign in

Prove the following statements. tanA/1-cotA+cotA/1-tanA=(secA.cosecA+1)

Note by Alok Patel 4 years, 1 month ago

Easy Math Editor

*italics*

_italics_

**bold**

__bold__

- bulleted- list

1. numbered2. list

paragraph 1paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)

> This is a quote

This is a quote

# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"

2 \times 3

2^{34}

a_{i-1}

\frac{2}{3}

\sqrt{2}

\sum_{i=1}^3

\sin \theta

\boxed{123}

Sort by:

Here's how I did it:

\(\frac{tanA}{1-cotA}\) + \(\frac{cotA}{1-tanA}\)

= \(\frac{\frac{sinA}{cosA}}{1-\frac{cosA}{sinA}}\) + \(\frac{\frac{cosA}{sinA}}{1-\frac{sinA}{cosA}}\)

= \(\frac{sin^{2}A}{cosA(sinA-cosA)}\) + \(\frac{cos^{2}A}{sinA(cosA-sinA)}\)

= \(\frac{sin^{3}A-cos^{3}A}{sinAcosA(sinA-cosA)}\)

= \(\frac{(sinA-cosA)(sin^{2}A+sinAcosA+cos^{2}A)}{sinAcosA(sinA-cosA)}\)

= \(\frac{sin^{2}A+sinAcosA+cos^{2}A}{sinAcosA}\)

= \(\frac{1+sinAcosA}{sinAcosA}\)

= \(1+\frac{1}{sinAcosA}\)

= 1 + secAcosecA

Hope you understood.

Log in to reply

Thank you to help me in problem solving

You are welcome!

In the right hand side of the equation, do you mean \(\text{sec A csc A + 1}\) or \(\text{sec A (csc A +1)}\)?

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestHere's how I did it:

\(\frac{tanA}{1-cotA}\) + \(\frac{cotA}{1-tanA}\)

= \(\frac{\frac{sinA}{cosA}}{1-\frac{cosA}{sinA}}\) + \(\frac{\frac{cosA}{sinA}}{1-\frac{sinA}{cosA}}\)

= \(\frac{sin^{2}A}{cosA(sinA-cosA)}\) + \(\frac{cos^{2}A}{sinA(cosA-sinA)}\)

= \(\frac{sin^{3}A-cos^{3}A}{sinAcosA(sinA-cosA)}\)

= \(\frac{(sinA-cosA)(sin^{2}A+sinAcosA+cos^{2}A)}{sinAcosA(sinA-cosA)}\)

= \(\frac{sin^{2}A+sinAcosA+cos^{2}A}{sinAcosA}\)

= \(\frac{1+sinAcosA}{sinAcosA}\)

= \(1+\frac{1}{sinAcosA}\)

= 1 + secAcosecA

Hope you understood.

Log in to reply

Thank you to help me in problem solving

Log in to reply

You are welcome!

Log in to reply

In the right hand side of the equation, do you mean \(\text{sec A csc A + 1}\) or \(\text{sec A (csc A +1)}\)?

Log in to reply